How often does deliberate self-harm occur relative to each suicide? A study of variations by gender and age. - Hawton, K; Harriss, L (2008)
Deliberate self-harm (DSH; i.e., nonfatal self-poisoning or self-injury) occurs much more frequently than suicide, yet there has been little detailed investigation of the comparative rates of DSH and suicide. We conducted a study of how rates of DSH relate to suicide rates across the life cycle by gender and by method of estimation of DSH rates, using 10 years of data from a local system for monitoring DSH presentations to a general hospital and national and local suicide statistics. The rate-ratio of DSH to suicide was 36 (95% CI 34.9-37.1) based on annual person-based rates of DSH episodes and was nearly five times higher in females (87.9; 95% CI 84.4-91.6) than in males (18.7; 95% CI 17.9-19.6). The ratio varied markedly across the life cycle, decreasing from more than 200 in teenagers to less than 10 in persons aged 60 years and over. The difference in the ratio between females and males also decreased over the life cycle. There were very similar findings when local suicide rates were used. These patterns were replicated when the data were analyzed, first, on the basis of all episodes of DSH during the study period, but with expectedly larger DSH:suicide ratios (e.g., overall 52.7; 95% CI 51.4-54.1), and second, on the basis of individual persons only engaging in DSH during the study period, but with smaller ratios (e.g., overall 26.2; 95% CI 25.4-27.2). The DSH:suicide rate ratios for those with high and low suicidal intent were similar within age groups except for those aged 60 years and over, in whom there was a greater proportion of high intent acts. These findings illustrate how the nature of self-harming behavior may vary in intention across the life cycle and between the genders, and provide a basis for further comparative work of this kind.